(untitled) (Innovative professional education, 2025)
The article presents the definition of the features, characteristics, and conditions for applying the project method in the development of college teachers’ professional competence. The structure of the project learning technology was proposed. It included three stages (project launch; implementation; defense) and nine steps that reflected the components of real research activities. It was concluded that it was advisable to organize training sessions to develop teachers’ innovative knowledge, skills and abilities